Adapting a Picture Description Task for Grammatical Analysis in English–Spanish Bilingual Preschool Children. (May 2021) - Smith, Vanesa P.; Cano, Isabel; Lozada, Lisa; Summers, Connie
The purpose of this study was to assess the use of an adapted picture description task described by Eisenberg and Guo to explore the morphosyntactic error patterns of English–Spanish preschool simultaneous bilingual learners. Language samples were collected from 28 bilingual preschool children aged 3 to 5 years. Language samples were elicited in both English and Spanish using a series of pictures and elicitation questions/prompts. Twenty-one participants produced a language sample in only one language (16 in English and 5 in Spanish) and seven participants produced language samples in both languages. Language samples were analyzed for grammaticality and error types. There were a higher number of fragments, tense marker, and grammatical morphemes errors in English. In Spanish, the children demonstrated more argument structure and pronominal form errors than in English. The adapted picture description task demonstrated sensitivity to common errors in English and Spanish and shows promise for use with bilingual populations.